The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/hyp.11397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy balance closure adjustment methods by independent evapotranspiration estimates from lysimeters and hydrological simulations

Abstract: Non‐closure of the surface energy balance is a frequently observed phenomenon of hydrometeorological field measurements, when using the eddy‐covariance method, which can be ascribed to an underestimation of the turbulent fluxes. Several approaches have been proposed in order to adjust the measured fluxes for this apparent systematic error. However, there are uncertainties about partitioning of the energy balance residual between the sensible and latent heat flux and whether such a correction should be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 48 publications
2
43
1
Order By: Relevance
“…For all FLUXNET site data, an overall mean energy imbalance of about 20% was observed (Wilson et al, ), signifying that in contrast to the theoretical basis of energy conservation implicit in Equation , the nonturbulent fluxes exceed the turbulent fluxes. This energy balance gap is often associated with energy transport of large scale eddies, which is not quantified accurately with the EC method and a 30‐min averaging interval (Foken, ; Mauder et al, ). Foken () described difficulties of model calibration associated with the energy balance gap.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all FLUXNET site data, an overall mean energy imbalance of about 20% was observed (Wilson et al, ), signifying that in contrast to the theoretical basis of energy conservation implicit in Equation , the nonturbulent fluxes exceed the turbulent fluxes. This energy balance gap is often associated with energy transport of large scale eddies, which is not quantified accurately with the EC method and a 30‐min averaging interval (Foken, ; Mauder et al, ). Foken () described difficulties of model calibration associated with the energy balance gap.…”
Section: Methodsmentioning
confidence: 99%
“…Ingwersen, Imukova, Högy, & Streck, ); however, we decided to correct Q E by partitioning the energy balance residual (Δ Q ) according to the Bowen ratio β (Twine et al, ; Equation ) in order to adjust ET a . Using this closure procedure, we assume the scalar similarity of gas and heat exchange not only for small scale but also for large‐scale eddies (Foken, ; Mauder et al, ). The median diurnal course of β was determined from the flux data from July and August and used for the correction for every time of the day as it allows to represent the variation of β through the course of the day and it is robust against measurement uncertainties of individual flux measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive long‐term integrated observations in different compartments (atmosphere, hydrosphere, biosphere) of the terrestrial system are used to set up, further develop, and apply various process models for site‐ and regional‐scale or catchment‐scale simulations. The evaluation of the energy balance closure problem for evapotranspiration estimates (Mauder et al, 2018) and the methodology development to use commercial microwave links for precipitation quantification and improved discharge modeling (Smiatek et al, 2017) are prominent examples. TERENO Pre‐Alpine observations have been used in conjunction with physically based process models to examine the impacts of land cover–management and climate change on ecosystem‐atmosphere cycling of energy (e.g., large‐eddy simulation model PALM; Maronga et al [2015]), water (e.g., WaSiM and GEOtop; Kunstmann et al, 2006), as well as C and N (e.g., LandscapeDNDC; Haas et al [2013]).…”
Section: Lessons Learned and Future Perspectivesmentioning
confidence: 99%
“…Studies have shown that the surface temperature, outgoing longwave radiation, cooling rates, and frozen surface extent are sensitive to far-infrared surface emissivity [8,9]. z 0m and z 0h are defined as the height at which the wind speed becomes zero and at which the extrapolated air temperature is identical to the surface temperature over a homogeneous surface under neutral and thermally stratified conditions [10][11][12], respectively, and they are very important parameters for estimating the momentum, heat, and mass exchange between the surface and atmosphere [13][14][15][16][17][18][19]. They are generally estimated directly using the eddy covariance method and satellite data inversion technique [20,21].…”
Section: Introductionmentioning
confidence: 99%